Regulation of the immune response to pathogens 2 - O’Garra, Anne (Henry Stewart Talks, 2012)
Tuberculosis (TB) as a major human threat, T cells & cytokines in TB, Difficulties in dealing with TB, Resistant & susceptible TB mouse models, Potential regulatory roles for IL-10 and factors that regulate host responses in TB, "Latent TB" into active TB and distinct transcriptional signatures, Finding common transcriptional clusters across diseases, TB and type 1 IFN: Bacterial pathogen induction of IFN production and IFN-inducible genes present in active TB patients